2006
DOI: 10.1021/jf0522715
|View full text |Cite
|
Sign up to set email alerts
|

Regiospecific Flavonoid 7-O-Methylation with Streptomyces avermitilis O-Methyltransferase Expressed in Escherichia coli

Abstract: O-Methylation, commonly found in synthesis of secondary metabolites of plants and micro-organisms, appears to transfer a methyl group to the hydroxyl group of the recipient which increases the hydrophobicity of the recipient. O-Methyltransferase (OMT), , was isolated and characterized from Streptomyces avermitilis MA-4680. Its amino acid sequence showed 68% similarity with antibiotic C-1027 OMT and 53% similarity with the carminomycin 4-OMT. was expressed in E. coli as a His-tag fusion protein and showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 29 publications
(39 reference statements)
4
52
0
Order By: Relevance
“…In the case of F1-OMT in barley, the methylation activity on apigenin was three times higher than that on naringenin (20). In contrast, SaOMT-2 has broad substrate specificity and can catalyze the methylation of isoflavonoids as well as naringenin (21). Sakuranetin has not been identified in either barley or S. avermitilis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of F1-OMT in barley, the methylation activity on apigenin was three times higher than that on naringenin (20). In contrast, SaOMT-2 has broad substrate specificity and can catalyze the methylation of isoflavonoids as well as naringenin (21). Sakuranetin has not been identified in either barley or S. avermitilis.…”
Section: Discussionmentioning
confidence: 99%
“…Substrate Specificity of GST-OsNOMT-It was reported that F1-OMT and SaOMT-2 catalyze the methylation of several flavonoids, including naringenin (20,21). Therefore, we determined the substrate specificity of OsNOMT against several types of phenolic compounds, including flavonoids and isoflavonoids.…”
Section: Purification Of Osnomt From Oscomt1 and Maldi-tof-tof Analysmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of NRN to DHK was achieved in the presence of AT3G51240, but not with AT5G20400. On the other hand, it was reported that 7-O-methyltransferase from S. avermitilis (SaOMT) can efficiently convert isoflavanones, flavones, and flavanones, including NRN, into the corresponding 7-O-methylated derivatives (15). For this reason, we used the enzyme for further conversion of DHK into 7-OMA.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are exclusive activity, where 7-OMTs that use flavonoids as a substrate do not use isoflavonoids as a substrate and vice versa. But SaOMT2 from Streptomyces avemilitis uses not only flavonoids but also isoflavonoids as a substrate with almost the same preference (Kim et al 2006a). It seems that OMTs from microorganisms contain more flexibility than those from plants in regards to substrate specificity (Kopycki et al 2008;Lee et al 2006).…”
Section: Substrate Specificity and Regioselectivity Of Flavonoid Omtsmentioning
confidence: 99%